COORDINATION OF ENTREPRENEURSHIP AND STATE INTERESTS IN AGRICULTURE - Yerzhanova, Zh. K.; Kimatova, R. G.; Kubasheva, G. A. (ЗКАТУ им. Жангир хана, 2022)
The purpose of the article is to consider the possibilities of effective organization of entrepreneurship by defining the boundaries of the combination of public interests and private entrepreneurial interests in agriculture. The article analyzes the reporting data on the organization of entrepreneurship in agriculture in the Republic of Kazakhstan and the West Kazakhstan region. This article presents the conditions and conditions for the implementation of state interests through the effective organization of small businesses. The importance, place, and prospects of development of entrepreneurship in agriculture are given. In addition, the article presents the factors and risks that hinder the conduct of small businesses in the regions, measures to eliminate them and opportunities for effective organization of entrepreneurship, analyzing economic indicators in dynamics, the author's proposed mechanisms for improving state support for small businesses. The article uses the works of domestic and foreign scientists-economists. The results of the article can be used for the work of agricultural institutions, peasant farms and agricultural and scientific workers.
Yerzhanova, Zh. K. COORDINATION OF ENTREPRENEURSHIP AND STATE INTERESTS IN AGRICULTURE / Zh. K. Yerzhanova, R. G. Kimatova, G. A. Kubasheva . - Текст : непосредственный // Ғылым және білім: Қазіргі көзқарас жағдайындағы ғылым мен білімді дамытудың өзекті мәселелері: ХХІІ халықаралық ғылыми-практ. конф. материалдары (12 сәуір 2022 ж.) = Наука и образование: Актуальные вопросы развития науки и образования в условиях современных вызовов: мат. ХХІІ междунар. науч.-практ. конф. (12 апреля 2022 г.) = Science and education: topical issues of the development of sciense and education in the context of modern challenges: mat. of the XXII International Scientific and Practical Conf. (12 aptil 2022). - Уральск: ЗКАТУ им. Жангир хана. - 2022. - № 2 (67) : прил. № 2. - Р. 360-369 (Uralsk).
Keywords: government interest; small business; innovation; risk; economic growth; efficiency; зкату; научный журнал